Media Training for Africa: Is China Exporting its Journalism? - Jákup Emil Hansen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
As part of its growing engagement in the African media sector, China leads training courses for African journalists. This has sparked debate in recent years, with some noting that China is ranked at the bottom of press freedom indices. This policy brief reports the results of a one-month field study in Uganda involving interviews with local journalists who attended Chinese training programs for African journalists. These interviews provide insight into the purpose and goals of the training programs, their possible impact on African journalistic practices, and the overall implications on freedom of the press and democracy in Africa.
Keywords: 330